Análise das constatações e recomendações das auditorias nas instituições públicas no estado do Ceará no período 2008 A 2011 - Aranha, Cristina Maciel (2014)
From corporate data E-control systems and Payroll System for civil servants of the state of Ceará and Management Audit Reports prepared by the Controladoria e Ouvidoria Geral do Estado in the period 2008-2011, this study developed models that allowed estimate the probability of occurrence of irregularities and audit recommendations in public units of the State of Ceará. The estimates of the models for binary dependent variables showed that about 31% of audits showed irregularities above average, although in 35% of these audits recommendations above average were observed. The efficiency in commitments and in executed budget by the server of the public unit influence the reduction of the detected irregularities while the value executed by voluntary transfer of resources are related to increases in the number of audit findings and recommendations.